JONES TENDON TRANSFER MODIFICATION WITH ERWIN RAMAWAN TECHNIQUE - Erwin Ramawan; Teddy Heri Wardhana; Ansari Rahman (Journal Orthopaedi and Traumatology Surabaya)
Background: Drop hand is a clinical manifestation of radial nerve lesion that cause hand dysfunction. Jones tendon transfer is one of the therapeutic modalities in overcoming it with many modifications, but there is still no mutual agreement for which technique is the best. One of them is the Erwin Ramawan technique. The purpose of this study was to determine the differences in results before and after tendon transfer surgery with the Erwin Ramawan technique in patients with radial nerve lesions.